Safety of hydroimplantation: a foldable intraocular lens implantation without the use of an ophthalmic viscosurgical device - Studeny, Pavel; Hyndrak, Michal; Kacerovsky, Martin; Mojzis, Peter; Sivekova, Deli; Kuchynka, Pavel (European journal of ophthalmology, 2014)
PURPOSE: To compare the safety of a single-piece, foldable intraocular lens (IOL) hydroimplantation with that of a standard implantation using an ophthalmic viscosurgical device (OVD). METHODS: One hundred consecutive patients with bilateral age-related cataract surgery were enrolled into a prospective double-blind study. Each patient's first eye was randomly assigned to a standard implantation technique with an OVD or the hydroimplantation technique, while the fellow eye received the opposite technique. The main outcomes measured were endothelial cell loss, postoperative changes of intraocular pressure (IOP), and the frequency of complications. RESULTS: The reduction of endothelial cell density 1 month and 6 months after the surgery was 9.76% ± 13.5%, 10.7% ± 12.6%, respectively, in group A (OVD) and 9.07% ± 12.7%, 9.13% ± 13.7%, respectively, in group B (hydroimplantation). The differences were not statistically significant. The mean IOP 2 hours after surgery was 10.19 ± 6.78 mm Hg in group A and 9.92 ± 7.01 mm Hg in group B. Twenty-four hours and 1 month after surgery, the mean IOP was 14.52 ± 5.59 mm Hg and 13.21 ± 3.5 mm Hg, respectively, in group A, and 15.45 ± 5.77 mm Hg and 13.1 ± 3.44 mm Hg, respectively, in group B. The differences between groups A and B were not statistically significant. CONCLUSIONS: The hydroimplantation technique is a safe technique for single-piece foldable IOL implantation. There was no increase in intraoperative and postoperative complications compared with the standard implantation technique using an OVD.
Keywords: Female; nitrooční čočky; Viscosupplementation; viskosuplementy; ženské pohlaví; fakoemulzifikace; Intraocular Pressure; Tonometry, Ocular; peroperační komplikace; lidé; dvojitá slepá metoda; tonometrie oční; pooperační komplikace; Phacoemulsification; Aged, 80 and over; Lenses, Intraocular; úbytek endoteliálních buněk rohovky; nitrooční tlak; Corneal Endothelial Cell Loss; prospektivní studie; Double-Blind Method; Male; Postoperative Complications; Aged; Prospective Studies; Lens Implantation, Intraocular; Viscosupplements; lidé středního věku; senioři nad 80 let; viskosuplementace; senioři; mužské pohlaví; implantace nitrooční čočky; zraková ostrost; Visual Acuity; Intraoperative Complications; Middle Aged; Humans